Progressivism in the Perspective of Islamic Educational Philosophy - Rosita; Rachmad Soe’oed; Khojir (Universitas Muhammadiyah Palu, 2024)
he world of education needs progressivism that can not only realize and develop children's potential and interests through creating learning freedom through children's experiences directly in the community, but progressivism that can lead students to get closer to their God. This study uses the design of a review literature review method in which the literature taken is in accordance with the subject of discussion. With the aim of obtaining information related to progressivism in the perspective of Islamic educational philosophy. The results of the analysis show that: (1) According to the view of Islamic educational philosophy in learning practice, educators not only equip with materials about the world, but also emphasize aspects that are thick with religious nuances and full of divine dimensions, (2) Educators can apply the concept of pprogresivism to teaching methods and materials that are in line with Islamic values, such as speculative methods and contemplative (contemplative), analysis of concepts (language), truth and experience as well as normative (values), historical (historical) and scientific approaches to actual problems, so that children have awareness of worship, obedient and able to face various obstacles during their lives, (3) In Islamic education, it is important to provide provisions for students about things that are useful in life in the world through their learning experiences. So, the author suggests learning methods that are suitable for use in a process of western/Islamic education, namely the method of tours (study tours), projects, dialogues, discussions, experiments, fieldwork, field trips and practical experiences, where students can face and solve problems and can learn from these problems so that they have useful experiences in the hereafter armed with the hereafter.